Ionomic and proteomic changes highlight the effect of silicon supply on the nodules functioning of Trifolium incarnatum L. - Coquerel, Raphaël; Arkoun, Mustapha; Trouverie, Jacques; Bernay, Benoit; Laîné, Philippe; Etienne, Philippe (Frontiers in Plant Science, 2024)
Introduction Numerous studies have reported the beneficial effects of silicon (Si) in alleviating biotic or abiotic stresses in many plant species. However, the role of Si in Fabaceae facing environmental stress is poorly documented. The aim of this study is to investigate the effect of Si on physiological traits and nodulation efficiency in Trifolium incarnatum L. Methods Si was supplied (1.7 mM in the form of Na2SiO3) plants inoculated with Rhizobium leguminosarum bv trifolii and plant physiological traits and nodule ionomic and molecular traits were monitored over 25 days. Results Si supply promoted shoot biomass, the quantity of both Si and N in roots and shoots, and the number, biomass and density of nodules and their nitrogenase abundance which contribute to better dinitrogen (N2) fixation. Ionomic analysis of nodules revealed that Si supply increased the amount of several macroelements (potassium, phosphorus and sulfur) and microelements (copper, zinc and molybdenum) known to improve nodulation efficiency and N2 fixation. Finally, comparative proteomic analysis (+Si versus -Si) of nodules highlighted that Si modulated the proteome of both symbionts with 989 and 212 differentially accumulated proteins (DAPs) in the infected host root cells and their symbiont bacteria, respectively. Discussion Among the DAPs, the roles of those involved in nodulation and N2 fixation are discussed. For the first time, this study provides new insights into the effects of Si on both nodular partners and paves the way for a better understanding of the impact of Si on improving nodule function, and more specifically, on the nodules’ N2-fixing capacity.